Application of microcatheter shaping based on computational fluid dynamics simulation of cerebral blood flow in the intervention of posterior communicating aneurysm of the internal carotid artery - Xu, Gangqin; Ba, Yueyang; Zhang, Kun; Cai, Dongyang; Yang, Bowen; Zhao, Tongyuan; Xue, Jiangyu (Frontiers in Neurology, 2023)
To investigate the application of aneurysm embolization microcatheter plasticity method based on Computational Fluid Dynamical CFD to simulate cerebral blood flow in the interventional treatment of posterior communicating aneurysms of the internal carotid artery, and to evaluate its practicality and safety. Twenty patients with posterior internal carotid artery communicating aneurysm who used CFD to simulate cerebral flow lines from January 2020 to December 2022 in our hospital were analyzed, and microcatheter shaping and interventional embolization were performed according to the main cerebral flow lines, and the success rate, stability and the effect of microcatheter in place were analyzed. Among the 20 patients, the microcatheters were all in place smoothly and the catheters were stable during the in vitro model test, and the microcatheters were all in place smoothly during the operation, with a success rate of 100%, and the catheter tips were stable and well supported intraoperatively, and no catheter prolapse, etc. The aneurysm was completely embolized in 19 cases immediately after surgery, and a small amount of the aneurysm neck remained in one case. There were no intraoperative complications related to the embolization catheter operation. Microcatheter shaping based on CFD simulation of cerebral blood flow, with precise catheter shaping, the high success rate in place, stability, and good support, greatly reduces the difficulty of catheter shaping and is worthy of further study and exploration.